Fe1‐xCoxS2 Solid Solutions with Tunable Energy Structures to Enhance the Performance of Triiodide Reduction in Dye‐Sensitized Solar Cells. Issue 10 (11th July 2018) - Ma, Dui; Zai, Jiantao; Wang, Yan; Qiao, Qiquan; Qian, Xuefeng
Abstract: The electrocatalytic performances of semiconductors are closely correlated to their energy structures, and solid solutions can continuously tune the energy structures by controlling their composition. Herein, a series of Fe1‐x Cox S2 (x=0–0.5) solid solutions have been synthesized and served as counter electrodes in dye‐sensitized solar cells (DSSCs). The Fermi level of Fe1‐x Cox S2 solid solutions shifted negatively as the x value changed from 0 to 0.5, and the electrocatalytic performance for I3 − reduction gradually enhanced due to the facilitated electron transfer process from electrode to I3 − . Benefitting from its negative Fermi level, Fe0.5 Co0.5 S2 exhibited the smallest charge transfer resistance ( Rct ) and remarkable electrocatalytic properties. The DSSCs using Fe0.5 Co0.5 S2 as a counter electrode achieve the lowest Rct (0.84 Ω cm 2 ) and the highest power conversion efficiency ( η =8.36%) of these solid solution materials. Abstract : Solar power : The energy structures of solid solutions can be adjusted to improve the electrocatalytic reduction of I3 −, which can offer an alternative approach to enhance the performance of dye‐sensitized solar cells.